Entre a ordem legitimadora da dominação e a esperança de libertação : um estudo sobre o conceito de pobre em Jon Sobrino - Aguiar, Jorge Roberto de Araújo (2011)
In this work, we exanimated the meaning of "poor" in The Principle of Mercy, from Jon Sobrino, according to Pierre Bourdieu. The idea of poor of God's Sacrament has been transmitted for a long tradition. This tradition appears again in the Prophetic Christianism of the Theology of Libertation, especially in Jon Sobrino. We tried to put some aditional informations for a new hermeneutic of "poor" not as a sociological category, but as a Sacrament. The symbolic reason, in Jon Sobrino, is characterized for the gratuity; his symbolic fight tries to change the categories of observation and cares of the social world, the cognitive and evaluates structures. This work is based in four moments. The first one has the focus on some questions about methodology and theory of research, mainly in the Theory of symbolic power, social space and symbolic violence in Pierre Bourdieu, that will be used to understand the "poor" in Jon Sobrino. In the second moment we will check as many as possible the word "poor" in the symbolic theory of domination according to Pierre Bourdieu. In the third moment, we will try to analyze the representations about poverty based on some representants of Theology's Libertation, in Latin America, connecting them with Jon Sobrino. Finally, we will check the semantic transformation of the word "poor" in Principle on Mercy